Digitalization of public consultations in rural municipalities of the Wielkopolskie Voivodship - Piotr Glenc (Rozwój Regionalny i Polityka Regionalna)
The development of e-participation and e-consultations is particularly characteristic of large cities, which is why researchers tend to focus on larger urban areas. This article adopts a different perspective. It presents the results of research aimed at identifying digital solutions used in public consultations in rural municipalities of the Wielkopolskie Voivodship (Poland), as well as determining the extent to which these solutions have been disseminated. An analysis was conducted on the resolutions adopted by individual municipalities that define the principles and procedures for conducting consultations with residents. The results indicate that the investigated municipalities declare the use of only a small fraction of the broad range of tools developed thus far in the field of e-consultations. Among the various stages of public consultation, the fewest opportunities for using digital solutions exist at the stage of submitting a request to hold a consultation process. Noteworthy is the limited use of mobile applications and social media, as well as the absence of declarations regarding the use of artificial intelligence solutions, which today offer significant opportunities for improving both the consultation process itself and the analysis of its results. Additionally, the study shows that in some municipalities more electronic communication channels are used at the stage of informing about ordered consultation than at announcing its outcomes.